Optic Foraminotomy for Clipping of Superior Carotid-Ophthalmic Aneurysms - Baldoncini, Matias; Luzzi, Sabino; Giotta Lucifero, Alice; Flores-Justa, Ana; González-López, Pablo; Campero, Alvaro; Villalonga, Juan F.; Lawton, Michael T. (Frontiers in Surgery, 2021)
Background: Carotid-ophthalmic aneurysms usually cause visual problems. Its surgical treatment is challenging because of its anatomically close relations to the optic nerve, carotid artery, ophthalmic artery, anterior clinoid process, and cavernous sinus, which hinder direct access. Despite recent technical advancements enabling risk reduction of this complication, postoperative deterioration of visual function remains a significant problem. Therefore, the goal of preserving and/or improving the visual outcome persists as a paramount concern. Objective: We propose optic foraminotomy as an alternative microsurgical technique for dorsal carotid-ophthalmic aneurysms clipping. As a secondary objective, the step by step of that technique and its benefits are compared to the current approach of anterior clinoidectomy. Methods: We present as an example two patients with superior carotid-ophthalmic aneurysms in which the standard pterional craniotomy, transsylvian approach, and optic foraminotomy were performed. Surgical techniques are presented and discussed in detail with the use of skull base dissections, microsurgical images, and original drawings. Results: Extensive opening of the optic canal and optic nerve sheath was successfully achieved in all patients allowing a working angle with the carotid artery for correct visualization of the aneurysm and further clipping. Significant visual acuity improvement occurred in both patients because of decompression of the optic nerve. Conclusion: Optic foraminotomy is an easy and recommended technique for exposing and treating superior carotid-ophthalmic aneurysms and allowing optic nerve decompression during the first stages of the procedure. It shows several advantages over the current anterior clinoidectomy technique regarding surgical exposure and facilitating visual improvement.